2017
DOI: 10.1590/0103-8478cr20151485
|View full text |Cite
|
Sign up to set email alerts
|

Infection of silkworm larvae by the entomopathogenic fungus Metarhizium anisopliae

Abstract: The isolate E9 of Metarhizium anisopliae was used in commercial hybrids of Bombyx mori larvae to evaluate its biological effect. Symptomatological analyses showed typical signs of fungal infection. Histopathology revealed the presence of large numbers of hemocytes in the hemocoel, and on the sixth dpi the bodies of the insects appeared to be colonised by the fungus. The isolate E9 is pathogenic to larvae B. mori and; therefore, death of the insects was caused by the colonization of fungus in the epidermal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…Traditionally, studying fungal burden in infected silkworms was limited to the usage of transgenic fungal mutants expressing fluorescent proteins [ 19 , 23 ], or to the application of time-consuming histological staining procedures [ 24 , 25 ]. To circumvent these limitations, we established a simple staining protocol using a common fluorescent dye, CW, to stain the cell wall of fungal hyphae in freshly extracted organs of A. fumigatus -infected silkworms, as demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, studying fungal burden in infected silkworms was limited to the usage of transgenic fungal mutants expressing fluorescent proteins [ 19 , 23 ], or to the application of time-consuming histological staining procedures [ 24 , 25 ]. To circumvent these limitations, we established a simple staining protocol using a common fluorescent dye, CW, to stain the cell wall of fungal hyphae in freshly extracted organs of A. fumigatus -infected silkworms, as demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There, following the disease progression relied on recombinant fungal strains that express fluorescent proteins. In the case of detecting non-fluorescent fungal strains in silkworms, Grocott-Gomori’s methenamine silver stain and periodic acid-Schiff stain, both of which are time-consuming, have been employed for the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae , respectively [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of commercial silkworm hybrids showed that a strain of Metarhizium anisopliae (Metschn.) Sorokīn (Ascomycota: Hypocreales) is an important pathogen of the silkworm (Ribeiro et al, 2017). Although governments and different organizations organize different programs and provide support to inform farmers and control these diseases, crop losses are not yet controlled as expected.…”
Section: Introductionmentioning
confidence: 99%
“…Metarhizium anisopliae (Metschnikoff) Sorokin (Hypocreales: Clavicipitaceae) é um fungo entomopatogênico, amplamente utilizado na agricultura devido à capacidade de se adequar a ambientes heterogêneos. Essa espécie pode infectar uma diversa variedade de insetos devido principalmente à evolução de genes que provocam a degradação da cutícula do hospedeiro, desintoxicação e biossíntese de toxinas (DORIN et al, 2015;RIBEIRO et al, 2017). O fungo M. anisopliae ganhou atenção dos pesquisadores brasileiros ao ser notado sua ocorrência epizoótica sobre a espécie Mahanarva posticata (Stal) (Hemiptera: Cercopidae), conhecida popularmente como a cigarrinha da folha da cana-de-açúcar (OLIVEIRA et al, 2016).…”
Section: Metarhizium Anisopliaeunclassified